Extracellular matrix proteins are time‐dependent and regional‐specific markers in experimental diffuse brain injury. Issue 9 (23rd July 2020) - Griffiths, Daniel R.; Jenkins, Taylor M.; Addington, Caroline P.; Stabenfeldt, Sarah E.; Lifshitz, Jonathan
Abstract: Introduction: The extracellular matrix (ECM) provides structural support for neuronal, glial, and vascular components of the brain, and regulates intercellular signaling required for cellular morphogenesis, differentiation and homeostasis. We hypothesize that the pathophysiology of diffuse brain injury impacts the ECM in a multi‐dimensional way across brain regions and over time, which could facilitate damage and repair processes. Methods: Experimental diffuse TBI was induced in male Sprague‐Dawley rats (325–375 g) by midline fluid percussion injury (FPI); uninjured sham rats serve as controls. Tissue from the cortex, thalamus, and hippocampus was collected at 15 min, 1, 2, 6, and 18 hr postinjury as well as 1, 3, 7, and 14 days postinjury. All samples were quantified by Western blot for glycoproteins: fibronectin, laminin, reelin, and tenascin‐C. Band intensities were normalized to sham and relative to β‐actin. Results: In the cortex, fibronectin decreased significantly at 15 min, 1 hr, and 2 hr postinjury, while tenascin‐C decreased significantly at 7 and 14 days postinjury. In the thalamus, reelin decreased significantly at 2 hr, 3 and 14 days postinjury. In the hippocampus, tenascin‐C increased significantly at 15 min and 7 days postinjury. Conclusion: Acute changes in the levels of these glycoproteins suggest involvement in circuit dismantling, whereas postacute levels may indicate a restorative or regenerative response associated with recovery from TBI. Abstract : The extracellular matrix (ECM) provides structural support for neuronal, glial, and vascular components of the brain, and regulates intercellular signaling required for cellular morphogenesis, differentiation, and homeostasis. We hypothesize that the ECM is susceptible to degradation and accumulation of glycoproteins, which can serve as spatial–temporal biomarkers of diffuse traumatic brain injury (TBI).